Respuesta :

Hi!

How do we use the substitution method?

To solve using the substitution method, we first want to isolate any of the variables from one of two equations, and then you take the value of that and plug it into the other equation.

Given:

[tex]y=4x-10[/tex]

[tex]y=-3x+4[/tex]

Step One:

Normally, our step one would be to pick a variable and isolate it, but it looks like we already have the y-value in both equations isolated! So our step one is already done!

Step Two:

Plug the isolated variable into the other equation.

We will use the value of y in the first one, and plug it into the second.

The value of y is "4x - 10", so we will change "y" in the second equation to "4x - 10", like so:

[tex]4x-10=-3x+4[/tex]

Step Three:

Algebra!

You should be familiar with how to solve equations.

So:

[tex]4x-10=-3x+4[/tex]

Add 10 to both sides:

[tex]4x=-3x+14[/tex]

Add 3x to both sides:

[tex]7x=14[/tex]

Divide both sides by 7:

[tex]x=2[/tex]

The last step!

Now, take the x value and plug it into one of the other equations and solve for y.

[tex]y=4(2)-10[/tex]

[tex]y=8-10[/tex]

[tex]y=-2[/tex]

Therefore, our answer is (2, -2).

For a fantastic explanation of how to do the substitution method, see:

https://brainly.com/question/26094713

ACCESS MORE